2005
DOI: 10.1021/la046820x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Composition and Orientation in Myelin Figures Characterized by Coherent Anti-Stokes Raman Scattering Microscopy

Abstract: The molecular organization inside myelin figures of various surfactants are studied by laser scanning coherent anti-Stokes Raman scattering (CARS) microscopy that permits three-dimension vibrational imaging. The resonant CARS signals from CH2 and H2O stretch vibrations are used to probe the surfactant and water molecules inside the myelin figures formed of C12E3, lecithin, and Aerosol OT. The polarization sensitivity of CARS is used to analyze the orientation of the CH2 groups and the H2O molecules. The CARS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 40 publications
3
53
0
1
Order By: Relevance
“…The main advantage of CARS over fluorescence microscopy is that no special dye staining is necessary because CARS utilizes Raman scattering from studied chemicals with specific vibration resonances. Chemically-selective imaging of molecular orientations in biological and lyotropic systems by CARS microscopy has been recently reported [8][9][10][11][12][13][14][15][16]. This technique has allowed for nondestructive visualization of both chemical composition and molecular orientations in the heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of CARS over fluorescence microscopy is that no special dye staining is necessary because CARS utilizes Raman scattering from studied chemicals with specific vibration resonances. Chemically-selective imaging of molecular orientations in biological and lyotropic systems by CARS microscopy has been recently reported [8][9][10][11][12][13][14][15][16]. This technique has allowed for nondestructive visualization of both chemical composition and molecular orientations in the heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Electron micrographs [24,26] showed that each tubular myelinic figure in the egg-yolk phosphatidylcholine/water system consisted of a water core surrounded by many concentric bilayers. More recently Raman spectroscopy techniques have confirmed the concentric bilayer arrangement [1,18]. Myelinic figures are not equilibrium structures, however, and eventually break up to form vesicles or other lamellar structures.…”
Section: Pure Surfactants With Low Solubility: Myelinic Figuresmentioning
confidence: 98%
“…Ráadásul ennél a módszernél arra sincs szükség, hogy azok természetes fluoreszcenciával rendelkezzenek (30). A módszer segítségével számos biológiai mintázat azonosítható, mint például a lipid kettôs rétegek (31), zsírsejtek (32), víz (33), DNS (34) vagy az idegsejteket burkoló myelinhüvely (35). A bôr vizsgálata során a CARS mikroszkópia alkalmas lehet az intracelluláris lipidek, vagy a szubkutisban található zsírsej-tek (2f.…”
Section: áBraunclassified